BDNF-loaded chitosan-based mimetic mussel polymer conduits for repair of peripheral nerve injury - Li, Lei; Chu, Ziyue; Li, Shihao; Zheng, Tong; Wei, Shusheng; Zhao, Yunpeng; Liu, Peilai; Lu, Qunshan (Frontiers in Cell and Developmental Biology, 2024)
Care for patients with peripheral nerve injury is multifaceted, as traditional methods are not devoid of limitations. Although the utilization of neural conduits shows promise as a therapeutic modality for peripheral nerve injury, its efficacy as a standalone intervention is limited. Hence, there is a pressing need to investigate a composite multifunctional neural conduit as an alternative treatment for peripheral nerve injury. In this study, a BDNF-loaded chitosan-based mimetic mussel polymer conduit was prepared. Its unique adhesion characteristics allow it to be suture-free, improve the microenvironment of the injury site, and have good antibacterial properties. Researchers utilized a rat sciatic nerve injury model to evaluate the progression of nerve regeneration at the 12-week postoperative stage. The findings of this study indicate that the chitosan-based mimetic mussel polymer conduit loaded with BDNF had a substantial positive effect on myelination and axon outgrowth. The observed impact demonstrated a favorable outcome in terms of sciatic nerve regeneration and subsequent functional restoration in rats with a 15-mm gap. Hence, this approach is promising for nerve tissue regeneration during peripheral nerve injury. mismatch between graft and nerve tissue size, and postoperative complications such as scar tissue invasion due to the migration of fibroblasts into the separation zone. Therefore, it is difficult to repair defective peripheral nerves(